2018
DOI: 10.1111/1751-7915.13353
|View full text |Cite
|
Sign up to set email alerts
|

Microbial communities in swine lungs and their association with lung lesions

Abstract: Summary Under natural farming, environmental pathogenic microorganisms may invade and affect swine lungs, further resulting in lung lesions. However, few studies on swine lung microbiota and their potential relationship with lung lesions were reported. Here, we sampled 20 pigs from a hybrid herd raised under natural conditions; we recorded a lung‐lesion phenotype and investigated lung microbial communities by sequencing the V3‐V4 region of 16S rRNA gene for each individual. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
40
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(48 citation statements)
references
References 73 publications
(91 reference statements)
8
40
0
Order By: Relevance
“…Previously, we found that Mycoplasma was the most abundant and only bacteria signi cantly associated with lung lesions in pigs (3). Similarly, we found that the pattern of correlations of Mycoplasma with six hematological parameters including RDW-SD, NLR, NEUR, LYMR, MCHC, and LYM was similar to the lung lesion correlations.…”
Section: Immune and Hematological Traits Associated With Lung Mycoplasupporting
confidence: 78%
See 3 more Smart Citations
“…Previously, we found that Mycoplasma was the most abundant and only bacteria signi cantly associated with lung lesions in pigs (3). Similarly, we found that the pattern of correlations of Mycoplasma with six hematological parameters including RDW-SD, NLR, NEUR, LYMR, MCHC, and LYM was similar to the lung lesion correlations.…”
Section: Immune and Hematological Traits Associated With Lung Mycoplasupporting
confidence: 78%
“…The amplicons were then puri ed and sequenced on an Illumina MiSeq sequencing platform (Illumina, SanDiego, CA, USA). The raw sequence reads were ltered as previously described (3). The Operational taxonomic units (OTUs) were clustered using UCLUST cluster algorithm in USEARCH v7.01090 (8).…”
Section: Measurement Of the Lung Lesions And Microorganism Levelsmentioning
confidence: 99%
See 2 more Smart Citations
“…The methodology employed in all these studies, however, remains largely the same regardless of the host. Interesting examples of non‐human microbial population studies are the works recently published in Microbial Biotechnology highlighting the implication of the imbalance of microbial flora from different anatomic sites with lesions and diseases (Huang et al ., ), or the relatedness between changes in diet with changes in the microbiome in different species (Simons et al ., ; Walburn et al ., ). As stated above, linking changes in microbial communities with human diseases is a hot spot in microbial population studies.…”
mentioning
confidence: 99%